Morphological evaluation of scar tissue and corneal layers after penetrating eye injury - Ivanchenko M.V.; Galayda N.A. (Морфологія, 2015)
Background. Penetrating eye injuries are the most serious damage in ocular trauma. They constitute, according to different authors, from 41,4% to 93,5% in the structure of ocular injuries. Corneal penetrating injury accounts 22,5-63%. Objective. Histologic and ultrastructural evaluations of scar in the cornea after penetrating eye injury. Methods. As the object of the study were used corneas over 12 month after penetrating corneal injury. The corneas were trisected and processed for conventional histologic analysis and transmission electron microscopy. Results. This study showed that the thickness of the cornea at the site of the scar after penetrating trauma over 9-12 months was less on 24.2% than in the adjacent intact tissue. Scaring tissue did not contain normal lamellae and lost their correct orientation. Stroma of the scar was composed from disorganized tightly packed fibrils and connective tissue cells (keratocytes and myofibroblasts). Conclusion. The repair of the cornea accompanied by specific problems: disorganization of the stroma reduces cornea transparency; contraction of fibrous scar tissue during the remodeling leads to optical aberrations. On the other hand, such a dense structure of the scar provides a relatively favorable condition for the reconstruction and reorganization of adjacent areas of the stroma and may also inhibit swelling of the stroma. Corneal wound healing occurs through a series of steps: activation of repair (corneal injury, proliferation and migration of corneal epithelial cells, stromal keratocytes, endothelial cells; cellular differentiations with active reduction, synthesis and accumulation of extracellular matrix) and tissue remodeling. Citation: Ivanchenko MV, Galayda NA. [Morphological evaluation of scar tissue and corneal layers after penetrating eye injury]. Morphologia. 2015;9(4):31-6. Russian.